PV system based Dynamic Voltage Restorer (DVR) in water pumping system for agricultural application / Awais Farooqi … [et al.] - Farooqi, Awais Farooqi; Othman, Muhammad Murtadha; Musirin, Ismail; Abdul Latip, Mohd Fuad Abdul Latip; Mohd Radzi, Mohd Amran; Z.Abidin, Izham; Sasi Mohammed, Daw Saleh (Universiti Teknologi MARA, 2021)
Modern solar-powered pumping systems are already being utilized in various fields and industrial applications especially in agricultural water irrigation systems where pumping water at a remote location is required with fewer electricity accessibility from the grid is not feasible. PV solely depends on solar hours per day, and it is not reliable when a location exhibits variable weather conditions, such as in Malaysia, having 12 solar hours daily but maximum 5-6 peak performance hours are as usually achieved due to the cloudy and rainy nature of the weather. In this case, PV-grid is not able to generate power as per daily demand and would create voltage sags, swell, and power outage when it is directly connected with the water pumping system for irrigation. To overcome this problem, a PV-DVR solar water pumping system (PV-DVRWP) is proposed in this paper that can mitigate power quality issues arising from PV-grid side such as voltage sags, voltage swells, and power outage by injecting the required amount of voltage into the line to maintain constant load voltage supply. The DVR controller strategy uses dq-abc frame mechanism to extract fault signals by using Park’s transformation method, PID, and hysteresis band PWM signal generator to drive the inverter of DVR connected with a battery storage system. The proposed methodology of the PVDVRWP system mitigates power quality issues occurring from the PV-grid side by injecting compensating voltage as well as being able to support water pumping systems in case of power outage for a three-phase system.